Interobserver reliability of teledermatology across all Fitzpatrick skin types. (January 2017) - Altieri, Lisa; Hu, Jenny; Nguyen, Andrew; Cockburn, Myles; Chiu, Melvin; Cotliar, Jonathan; Kim, Jenny; Peng, David; Crew, Ashley
Introduction: Demand for dermatologic services in safety net hospitals, which disproportionately serve patients with darker coloured skin, is growing. Teledermatology has the potential to increase access and improve outcomes, but studies have yet to demonstrate the reliability of teledermatology for all Fitzpatrick skin types. Methods: We assessed the reliability of teledermatologists' diagnoses and management recommendations for store-and-forward teledermatology in patients with lightly pigmented (Fitzpatrick skin types I–III) versus darkly pigmented (Fitzpatrick skin types IV–VI) skin, when compared to in-person diagnosis and management decisions. This prospective study enrolled 232 adult patients, presenting with new, visible skin complaints in a Los Angeles county dermatology clinic. Forty-seven percent of patients were Fitzpatrick skin types I–III, and 53% were Fitzpatrick skin types IV–VI. Results: Percent concordance for the identical primary diagnosis was 53.2% in lighter (Fitzpatrick I–III) skin types and 56.0% in darker (Fitzpatrick IV–VI) skin types. There was no statistically significant difference in concordance rates between lighter and darker skin types for primary diagnosis. Concordance rates for diagnostic testing, clinic-based therapy, and treatments were similar in both groups of Fitzpatrick skin types. Discussion: These results suggest that teledermatology is reliable for the diagnosis and management of patients with all Fitzpatrick skin types.